The B subunit of the DNA polymerase alpha-primase complex in Saccharomyces cerevisiae executes an essential function at the initial stage of DNA replication. - Foiani, M (1994)
The four-subunit DNA polymerase alpha-primase complex is unique in its ability to synthesize DNA chains de novo, and some in vitro data suggest its involvement in initiation and elongation of chromosomal DNA replication, although direct in vivo evidence for a role in the initiation reaction is still lacking. The function of the B subunit of the complex is unknown, but the Saccharomyces cerevisiae POL12 gene, which encodes this protein, is essential for cell viability. We have produced different pol12 alleles by in vitro mutagenesis of the cloned gene. The in vivo analysis of our 18 pol12 alleles indicates that the conserved carboxy-terminal two-thirds of the protein contains regions that are essential for cell viability, while the more divergent NH2-terminal portion is partially dispensable. The characterization of the temperature-sensitive pol12-T9 mutant allele demonstrates that the B subunit is required for in vivo DNA synthesis and correct progression through S phase. Moreover, reciprocal shift experiments indicate that the POL12 gene product plays an essential role at the early stage of chromosomal DNA replication, before the hydroxyurea-sensitive step. A model for the role of the B subunit in initiation of DNA replication at an origin is presented.